Efficacy of Intravenous Ibuprofen Versus Intravenous Ketorolac in the Management of Post-Operative Pain after Abdominal Surgeries (Medical Forum Monthly, 2022)
Objective: To identify the difference in post-operative pain control among patients undergoing abdominal surgeries with intravenous Ibuprofen compared to intravenous Ketorolac.Study Design: Randomized controlled trial studyPlace and Duration of Study: This study was conducted at the Pakistan Air Force Hospital, Base Faisal, Fazaia Ruth Pfau Medical College, Karachi from January 2021 to July 2021.Materials and Methods: A total of 68 patients undergoing abdominal surgeries, were randomly assigned in 1:1 ratio to receive 800 mg IV-ibuprofen or 30 mg IV-ketorolac every 6 hours, first dose being given immediately after surgery. Visual analogue scores for pain at rest and pain at ambulation were assessed at 24 hours after surgery. Additional requirement of opioid analgesia (IV nalbuphine) was also recorded.Results: There were 34 patients in Ibuprofen group and 34 patients in ketorolac group. The mean VAS pain score at rest for the Ibuprofen Group (Group A) was 2.7 whereas for the Ketorolac Group (Group B) it was 2.9 (p value 0.482). The mean VAS pain score at movement for the Ibuprofen Group (Group A) was 3.00 and for the Ketorolac Group (Group B) was 3.33 (p value 0.382).Conclusion: It is concluded that Intravenous Ibuprofen can be used for post-operative analgesia with efficacy equal to ketorolac. This has also been recorded that administration of Ibuprofen leads to decreased opioid consumption for pain relief thus minimizing the risks associated with opioid analgesia. This is a single center study, we would need further studies to validate the findings.